The Cultural Heritage of the Ancient Russian City of Yelets - Yudina, Tatyana; Merkulova, Alexandra (Slavica, 2022)
This article provides scholarly evidence the small historical city of Yelets as a potential cultural heritage site in the context of its socio-cultural significance for the state, society and the local community. The paper overviews the results of a comprehensive sociological study of the issues of the cultural heritage of this ancient Russian city. The issues of the cultural heritage of Yelets is considered from the perspective of internal and external identification processes which transformed it and make it lose its unique urban identity. For the analysis of cultural heritage, the types of identity of the city are identified: historical and cultural, visual and spatial, socio-psychological and communicative spatial. The main factors of the identification processes of the city are analyzed, such as urban identity, history, culture, social interaction and language.